A Touchscreen Motivation Assessment Evaluated in Huntington's Disease Patients and R6/1 Model Mice - Heath, Christopher J.; O'Callaghan, Claire; Mason, Sarah L.; Phillips, Benjamin U.; Saksida, Lisa M.; Robbins, Trevor W.; Barker, Roger A.; Bussey, Timothy J.; Sahakian, Barbara J. (Frontiers in Neurology, 2019)
Apathy is pervasive across many neuropsychiatric disorders but is poorly characterised mechanistically, so targeted therapeutic interventions remain elusive. A key impediment has been the lack of validated assessment tools to facilitate translation of promising findings between preclinical disease models and patients. Apathy is a common symptom in Huntington’s disease. Due to its established genetic basis and the availability of defined animal models, this disease offers a robust translational framework for linking motivated behaviour with underlying neurobiology and an ideal context in which to evaluate a quantitative, translational apathy assessment method. In this study we therefore aimed to demonstrate the validity of using touchscreen-delivered progressive ratio tasks to mirror apathy assessment in Huntington’s disease patients and a representative mouse model. To do this we evaluated Huntington’s disease patients (n=23) and age-matched healthy controls (n=20), and male R6/1 mice (n=23) and wildtype controls (n=29) for apathy-like behaviour using touchscreen-delivered progressive ratio tasks. The primary outcome measure of the assessment was breakpoint, defined as the highest number of touchscreen responses emitted before task engagement ceased. Patients and R6/1 mice were both found to exhibit significantly reduced breakpoints relative to their respective control groups, consistent with apathy-like behaviour. This performance was also not associated with motoric differences in either species. These data demonstrate the utility of touchscreen-delivered progressive ratio tasks in detecting clinically relevant motivational deficits in Huntington’s disease. This approach may offer a platform from which clinically relevant mechanistic insights concerning motivation symptoms can be derived and provide an effective route for translation of promising preclinical findings into viable therapeutic interventions.